PENGARUH PENGALAMAN KERJA, PELATIHAN, DAN TINGKAT PENDIDIKAN TERHADAP PROFESIONALISME PEGAWAI DINAS TENAGA KERJA KABUPATEN TABALONG - Sutrisno, Sutrisno; Firdaus, Firdaus (JURNAL KINDAI, 2025)
This study aims to analyze the effect of work experience, training, and education level on employee professionalism at the Manpower Office of Tabalong Regency, both simultaneously and partially, as well as to identify the dominant influencing variable. The research employed a quantitative approach using a survey method. The population consisted of 40 employees, with samples selected through random sampling. Data analysis was conducted using multiple linear regression. The results indicate that work experience, training, and education level simultaneously have a significant effect on employee professionalism. Partially, each variable also shows a significant influence on professionalism. Furthermore, work experience is identified as the most dominant factor affecting employee professionalism at the Manpower Office of Tabalong Regency. Keywords: work experience, training, education level, employee professionalism